Comparative Evaluation Of Efficacy Of Three Different Rotary Nickel Titanium Retreatment File Systems On Preserving Remaining Root Dentin Thickness Using Cone Beam Computed Tomography - An In Vitro Study (Journal of Pharmaceutical Negative Results, 2023)
Objective: To evaluate and compare the efficacy of different rotary retreatment file systems on preserving the remaining dentin thickness using cone beam computed tomography.Materials and methods: 36 single rooted, non carious mandibular premolars with straight single canals and closed apices were selected. All the teeth were prepared by the same operator using rotary files using an electric motor with the recommended torque and speed. Obturation was completed and CBCT images were taken at the coronal, middle and apical third and the buccolingual and mesiodistal dimensions were noted. The samples were then randomly allocated into 3 groups (n=12), Group I, Group II and Group III according to the retreatment kit used. A drop of gutta percha solvent was used in all the teeth. Post retreatment, the CBCT images were taken in the axial plane at the coronal, middle and apical one third. RDT was measured at the buccal, lingual, mesial and distal walls and compared. Statistical evaluation was done using Paired t test, One Way ANOVA and Post Hoc test.Conclusion: A statistically significant difference was present in the RDT after retreatment between all the 3 groups in coronal, middle and apical section. Maximum amount of RDT was conserved in Group III followed by Group I followed by Group II after retreatment.